Attitudes towards African traditional medicine and Christian spiritual healing regarding treatment of epilepsy in a rural community of northern Tanzania - Winkler, Andrea Sylvia; Mayer, Michael; Ombay, Michael; Mathias, Bartholomayo; Schmutzhard, Erich; Jilek-Aall, Louise (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Background: Most people with epilepsy (PWE) live in developing countries with limited access to health care facilities. In sub-Saharan Africa with over 40 million PWE, 90% do not receive adequate medical treatment. In this context, traditional medicine, being easily accessible, plays an important role. However, in sub-Saharan Africa, studies on the attitude of people (both affected and not affected by epilepsy) towards traditional medicine for treatment of epilepsy are scarce. Methods: In this study, 167 people (59 PWE, 62 relatives, 46 villagers) were interviewed at the hospital and in the community with a semi-structured validated questionnaire regarding the prevailing attitude towards traditional medicine for treatment of epilepsy in a rural area of northern Tanzania. Results: Various traditional healing methods (THM) could be ascertained, i.e. traditional herbal medicine, spiritual healing, scarifications and spitting. 44.3% (n=74/167) of the interviewed people were convinced that epilepsy could be treated successfully with THM. Interestingly, 34.1% (n=57/167) thought that Christian prayers could cure the cause and/or treat symptoms of epilepsy. Significantly more PWE and their relatives were in favour of THM compared to villagers not knowing about or not immediately affected by epilepsy (χ2-test, p=0.004). Further factors influencing people’s attitudes towards THM were gender, tribe, religion and urbanity of people’s dwellings. Conclusion: Our study demonstrates that not only THM but also prayers in the Christian sense seem to play an important role in people’s beliefs regarding successful treatment of epilepsy. Factors influencing this belief system have been identified and are discussed.